Deposit Insurance, Risk, and Market Power in Banking - Keeley, Michael C. (American Economic Review, 1990)
A fixed-rate deposit insurance system provides a moral hazard for excessive risk taking and is not viable absent regulation. Although the deposit insurance system appears to have worked remarkably well over most of its 50-year history, major problems began to appear in the early 1980's. This paper tests the hypothesis that increases in competition caused bank charter values to decline, which in turn caused banks to increase default risk through increases in asset risk and reductions in capital.